The Effect Of Soft Skill And Hard Skill On Work Readiness Of The 2018 STIE Jayakarta Students - Binton Siburian; Syifa Afifah; Parlin Tumpal Sinaga; Oktavia Marpaung (International Journal of Informatics, Economics, Management and Science (IJIEMS), 2022)
This study aims to determine the effect of soft skills and hard skills on the work readiness of STIE Jayakarta students batch 2018.The population of this research is STIE Jayakarta students class of 2018 and the sample is 38 students. Sampling by incidental sampling. The variables used are soft skills, hard skills and work readiness. Analysis of the data using multiple linear correlation regression analysis, which looks at the relationship between soft skills, hard skills and student work readiness, determines the closeness of the relationship between these variables and examines the effect of soft skills and hard skills on student work readiness, either partially or simultaneously.Partially, the results of the study indicate that there is no influence of soft skills on student work readiness, but there is an influence of hard skills on student work readiness. Meanwhile, from the results of simultaneous testing, it can be concluded that soft skills and hard skills together have an influence on student work readiness